Facebook Marketing of Nursing homes: A case study of a Pinetown Nursing Home - Nimmo, Tatum (The IIE, 2022)
The interest in marketing to the Generation X as an entirely different facet of a market has become more relevant to brands this decade (Designblendz, 2019). This study investigates Facebook, an affordable and effective means of marketing used to reach a specific audience whilst creating long-term relationships and potential brand loyalty. The study has the potential to assist existing brands such as TAFTA to better reach and interact with their target audience via Facebook Social Media Marketing. The research executed uncovered this hybrid generation, that has lived through a variety of marketing methods is skeptical of social media marketing and interacting with businesses they are not familiar with and therefore, it is essential for businesses to share their most real, human self-online, in order to effectively reach this audience. The methodology of this study made use of a qualitative research approach, whereby exploratory data was collected through digital surveys and semi-structured interviews with individuals responsible for the financial, security and wellbeing of the elderly family members. The data collected revealed deeper human truths, due to the human centric nature of the study, assisting the researcher to make use of and evaluate the likelihood of Social Media Marketing via Facebook being a beneficial marketing method for Nursing Homes in their attempts to attain new residents. The insights uncovered included real life examples, behaviour and emotions, as well as their opinion of existing Nursing Home advertisement methods. The idea of connectivity, security, affordability and comfort were the key insights identified, these will assist brands creating relevant content when making use of Social Media Marketing, these insights will also remain relevant throughout the study.
Keywords: Facebook; Social media; Marketing; Consumer behaviour